Is the COVID-19 pandemic masking the deadlier Lassa fever epidemic in Nigeria? (2020)
With the COVID-19 officially declared a pandemic, Nigeria alongside other countries is directing all its resources and manpower to contain this pandemic. However, the existence of Lassa fever (LF), a more severe, zoonotic, endemic and viral haemorrhagic fever caused by Lassa virus with higher case fatality ratio (CFR) rages on across Nigeria while receiving little or no public health attention. The simultaneously increasing cases of COVID-19 and LF across Nigeria would be catastrophic unless infection prevention and control measures toward both LF and COVID-19 outbreaks are considered alongside.